Menerima Orangnya, Menolak Dosanya: Suatu Pendekatan Kristen terhadap Kaum LGBT dalam Pandangan Letty M. Russell - Meiny Komalig; Ferry Lumintang (Sekolah Tinggi Alkitab Batu, Malang, 2026)
This article examines the Christian approach to the presence of LGBT people within the church through the theological perspective of Letty M. Russell. LGBT issues are a complex social and theological reality that creates tension between the church's fidelity to the moral teachings of the Bible and its call to live out Christ's inclusive love. This research employs a literature review method, examining various theological sources, particularly Letty M. Russell's thoughts on God's hospitality, justice as a right relationship, and contextual hermeneutics. The results demonstrate that the